Transmission of influenza A viruses - Neumann, Gabriele; Kawaoka, Yoshihiro (Virology (New York, N.Y.), 2015)
Influenza A viruses cause respiratory infections that range from asymptomatic to deadly in humans. Widespread outbreaks (pandemics) are attributable to ‘novel’ viruses that possess a viral hemagglutinin (HA) gene to which humans lack immunity. After a pandemic, these novel viruses form stable virus lineages in humans and circulate until they are replaced by other novel viruses. The factors and mechanisms that facilitate virus transmission among hosts and the establishment of novel lineages are not completely understood, but the HA and basic polymerase 2 (PB2) proteins are thought to play essential roles in these processes by enabling avian influenza viruses to infect mammals and replicate efficiently in their new host. Here, we summarize our current knowledge of the contributions of HA, PB2, and other viral components to virus transmission and the formation of new virus lineages. •HA receptor-binding specificity is important for virus transmissibility.•The polymerase complex is also important for virus transmissibility.•Avian influenza viruses may acquire the ability to transmit among mammals.